Rabies Hysteria: Case series - Shabansalmani, Nazanin; Fazeli, Maryam; Pourhossein, Behzad; Solgi, Atie; Bashar, Rouzbeh (Novelty in Biomedicine, 2024)
Background: Rabies is an acute and fatal zoonotic viral disease that affects warm-blooded mammals. This disease is usually transmitted between humans and other animals through bites, scratches, or saliva from infected animals. Depending on the mortality rate of rabies, people sometimes experience mental stress after biting or contact. This condition is called mental stress toward rabies (Rabies Hysteria). Cases Report: In this study, we referred to seven cases of rabies hysteria, which were referred to the WHO Collaborating Center for Reference and Research on Rabies of Pasteur Institute of Iran. Conclusion: Studies have shown that the level of low awareness and the wrong attitude toward the disease aggravates medical hysteria. The health system should evaluate social knowledge and attitude.